Radioprotective ingredients of a composite dairy product - Donskaja, G. A.; Krekker, L. G.; Kolosova, E. V.; Bychkova, T. S.; Karapetyan, V. K. (Vestnik MGTU, 2024)
Food products that have an anti-radiation effect and can be used in conditions of increased radiation are of particular interest. Scientifically based rationing of such products in the daily diet will make it possible to effectively use them to adapt the body to increased radiation and eliminate the effects of radiation exposure during treatment or examination. The purpose of the research presented in the paper is to analyze the nutritional and physiological causes of chronic nutrient deficiency of radioprotective microelements in the diet, to study the qualitative and biological characteristics of radioprotective ingredients to create a milk-based anti-radiation composition. The experimental part of the study has related to researching the mineral composition of selected ingredients and their antioxidant activity. The data obtained indicate that milk thistle flour contains a large amount of calcium, and sunflower meal contains potassium. In terms of potassium content, sunflower meal exceeds the microelement content in milk thistle by 50 %. The amount of calcium in milk thistle is 67 % higher compared to sunflower meal. In addition, plant raw materials are a source of magnesium, iron, zinc, copper, phosphorus and have pronounced antioxidant activity. As a result a scientific substantiation of the addition of ingredients for the production of radioprotective fermented milk product and its use in therapeutic and prophylactic nutrition for adults has been carried out in order to prevent radiation complications and remove radionuclides from the body. The normalized amount of ingredients for consumption per day has been calculated according to recommended diets, nutritional, physiological value, and physiological activity. Standards have been established for enriching micronutrients in the production of a radioprotective dairy product designed to increase the body's resistance to the action of free radical processes and enhance antioxidant capacity under conditions of radiation exposure.